Budgeting for Success - Kelly Elliot; Tim Kellison (University of Kansas Libraries, 2019)
There has been little research into the comparison of historically black colleges and universities (HBCUs) to predominantly white institutions (PWIs) in recent years.  With growing athletic department budgets, it is important to understand how HBCUs financially compare to their PWI counterparts.  Therefore, the purpose of this study was to determine how HBCU athletic departments compare to their peer PWIs in terms of athletic department spending and to conduct a budgetary analysis of HBCU athletic departments. To examine differences in athletics budgets, data were collected from the U.S. Department of Education's Equity in Athletics Disclosure Act (EADA) Survey.  NCAA member institution peer groups with HBCU members were selected for this study.  Institutional data include salary, recruitment, operation, and scholarship expenses and revenue for peer groups. An ANOVA was conducted to compare peer institutions, institutions in the same region, by division, and overall.  The results indicated HBCU peer groups are spending significantly less compared to their PWI counterparts.  Additionally, among HBCU institutions, most athletic programs are spending the most on athletic aid expenses.  Similarly, HBCUs are earning significantly less revenue compared to their peers. Athletic department administrators can use the results of this study to help create budgets comparable to peer institutions.